1972
DOI: 10.1128/aem.23.2.262-267.1972
|View full text |Cite
|
Sign up to set email alerts
|

Structures Suggesting Cell-Wall-Deficient Forms Detected in Circulating Erythrocytes by Fluorochrome Staining

Abstract: Cell-wall-deficient (CWD) forms of bacteria are associated with certain cases of idiopathic septicemia. In this preliminary study of blood examined immediately after venipuncture, structures with a morphology characteristic of CWD forms were seen parasitizing the erythrocytes. These inclusions were usually circumferential, but in some cases they protruded from the red cells. The CWD forms were detected by staining with Gould's rhodamine-labeled muramidase, which reacted similarly to acridine orange but with gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, as described by many studies, the vast majority of the bacteria found in blood cannot be cultured with existing techniques. This is due to several technical limitations (including inappropriate media and culture conditions) as well as biologic features of bacteria (including dormant forms and bacterial L‐forms). The bacterial DNA detected with our molecular techniques may correspond to free bacteria, bacteria associated with WBCs or RBCs as well as free bacterial DNA resulting from immune degradation.…”
Section: Discussionmentioning
confidence: 99%
“…However, as described by many studies, the vast majority of the bacteria found in blood cannot be cultured with existing techniques. This is due to several technical limitations (including inappropriate media and culture conditions) as well as biologic features of bacteria (including dormant forms and bacterial L‐forms). The bacterial DNA detected with our molecular techniques may correspond to free bacteria, bacteria associated with WBCs or RBCs as well as free bacterial DNA resulting from immune degradation.…”
Section: Discussionmentioning
confidence: 99%